The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.3200/jach.57.3.315-324
|View full text |Cite
|
Sign up to set email alerts
|

Illicit Use of Prescription ADHD Medications on a College Campus: A Multimethodological Approach

Abstract: This study supplies a rich understanding of the growing national trend of illegal ADHD stimulant use. The authors discuss strategies for stemming the tide of ADHD stimulant use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
298
7
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(340 citation statements)
references
References 20 publications
24
298
7
8
Order By: Relevance
“…A study on a large 2001 sample of undergraduate programs including institutions of different size, location, religious affiliation and private/public status, showed an almost 7% lifetime prevalence of nonmedical stimulant use (McCabe, Knight, Teter & Wechsler, 2005). Although this study did not distinguish between cognitive enhancement and other nonmedical uses, more recent surveys of college students have done so and indicate that cognitive enhancement is the primary motivation for most students using stimulants (e.g., DeSantis, Webb, & Noar, 2008; see Smith & Farah, 2011, for a review). These more recent studies also indicate substantially larger proportions of students using prescription stimulants compared to the McCabe and colleagues' estimates, although the samples have been smaller and less representative.…”
Section: Introductionmentioning
confidence: 59%
“…A study on a large 2001 sample of undergraduate programs including institutions of different size, location, religious affiliation and private/public status, showed an almost 7% lifetime prevalence of nonmedical stimulant use (McCabe, Knight, Teter & Wechsler, 2005). Although this study did not distinguish between cognitive enhancement and other nonmedical uses, more recent surveys of college students have done so and indicate that cognitive enhancement is the primary motivation for most students using stimulants (e.g., DeSantis, Webb, & Noar, 2008; see Smith & Farah, 2011, for a review). These more recent studies also indicate substantially larger proportions of students using prescription stimulants compared to the McCabe and colleagues' estimates, although the samples have been smaller and less representative.…”
Section: Introductionmentioning
confidence: 59%
“…Illicit use of ADHD medications on college campuses has also been the subject of considerable inquiry. A survey of more than 1800 undergraduates at a single university (DeSantis, Webb, & Noar, 2008) found that 34% of respondents endorsed having used ADHD medications illegally, though the authors cautioned that this rate was higher than those found in previous studies. A number of university counseling centers (e.g., see California State University, Fresno Student Health Center, 2013) have begun to refuse to provide ADHD evaluations for students (Schwarz, 2013b).…”
Section: Effects Of Symptom Thresholds On Outcomementioning
confidence: 73%
“…For example, DeSantis, Webb, and Noar (2008) reported that fraternity members are significantly more likely to use stimulant drugs than fraternity nonmembers. Energy drinks such as Red Bull were not included in their study, but they are technically a stimulant drug so their findings may well apply to energy drinks.…”
Section: Masculinity Energy Drink Use Jock Identity and Fraternitymentioning
confidence: 99%